2019
DOI: 10.1038/s41598-019-39591-7
|View full text |Cite
|
Sign up to set email alerts
|

Altered splicing and cytoplasmic levels of tRNA synthetases in SF3B1-mutant myelodysplastic syndromes as a therapeutic vulnerability

Abstract: Myelodysplastic syndromes (MDS) are haematopoietic malignancies that are characterised by a heterogeneous clinical course. In recent years, sequencing efforts have uncovered recurrent somatic mutations within RNA splicing factors, including SF3B1, SRSF2, U2AF1 and ZRSR2 . The most frequently mutated gene is SF3B1 , mutated in 17% of MDS patients. While SF3B1 mutations and their effects on splicing have been well charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 52 publications
2
20
0
Order By: Relevance
“…SF3B1 mutations have also been reported in solid tumors, including 20% of uveal melanomas (UM) [810], 3% of pancreatic ductal adenocarcinomas [11], and 1.8% of breast cancers [12]. RNA-sequencing (RNA-seq) analyses in different tumor types and cell lines with SF3B1 missense mutations, including the most prevalent substitution K700E, identified distinct alternative splicing (AS) defects [1315].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SF3B1 mutations have also been reported in solid tumors, including 20% of uveal melanomas (UM) [810], 3% of pancreatic ductal adenocarcinomas [11], and 1.8% of breast cancers [12]. RNA-sequencing (RNA-seq) analyses in different tumor types and cell lines with SF3B1 missense mutations, including the most prevalent substitution K700E, identified distinct alternative splicing (AS) defects [1315].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, CRISPR/Cas9 genome editing has allowed researchers to faithfully reproduce human pathological mutations in animal models. Human SF3B1 mutations have been introduced in cell lines [1518], but mimicking these mutations in multicellular organisms has only been achieved by conditional alleles in murine models [19]. Taking advantage of the extraordinary conservation of splicing factors across evolution and the ease of genetic manipulation of C .…”
Section: Introductionmentioning
confidence: 99%
“…First, diverse computational pipelines have been used to assess differences in alternative splicing between WT and SF3B1-mutated samples, resulting in distinct conclusions. For instance, Liberante et al reanalyzed previously published data and found that SF3B1 mutation was mostly associated with differential skipped exon events, rather than A3'SS selection (Liberante et al, 2019). Second, intronic elements directing splicing have evolved differently in C. elegans compared to other organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, CRISPR/Cas9 genome editing has allowed researchers to faithfully reproduce human pathological mutations in animal models. Human SF3B1 mutations have been introduced in cell lines (Alsafadi et al, 2016;Shiozawa et al, 2018;Gupta et al, 2019;Liberante et al, 2019), but mimicking these mutations in multicellular organisms has only been achieved by conditional alleles in murine models (Xu et al, 2019). Taking advantage of the extraordinary conservation of splicing factors across evolution and the ease of 6 Different sftb-1 missense mutations display additive effects when combined We edited the C. elegans genome to mimic the K700E mutation, the most frequent SF3B1 substitution in tumors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation